Population Structure of Riverine and Coastal Dolphins Sotalia fluviatilis and Sotalia guianensis: Patterns of Nuclear and Mitochondrial Diversity and Implications for Conservation. (25th September 2018) - Caballero, Susana; Hollatz, Claudia; Rodríguez, Sebastián; Trujillo, Fernando; Baker, C Scott
Abstract: Coastal and freshwater cetaceans are particularly vulnerable due to their proximity to human activity, localized distributions, and small home ranges. These species include Sotalia guianensis, found in the Atlantic and Caribbean coastal areas of central and South America, and Sotalia fluviatilis, distributed in the Amazon River and tributaries. We investigated the population structure and genetic diversity of these 2 species by analyses of mtDNA control region and 8–10 microsatellite loci. MtDNA analyses revealed strong regional structuring for S. guianensis (i.e., Colombian Caribbean vs. Brazilian Coast, F ST = 0.807, ΦST = 0.878, P < 0.001) especially north and south of the Amazon River mouth. For S. fluviatilis, population structuring was detected between the western and eastern Amazon (i.e., Colombian Amazon vs. Brazilian Amazon, F ST = 0.085, ΦST = 0.277, P < 0.001). Haplotype and nucleotide diversity were higher for S. fluviatilis. Population differentiation was supported by analysis of the microsatellite loci ( S. guianensis, northern South America vs. southern South America F ST = 0.275, Jost's D = 0.476, P < 0.001; S. fluviatilis, western and eastern Amazon F ST = 0.197, Jost's D = 0.364, P < 0.001). Most estimated migration rates in both species overlapped with zero, suggesting no measurable migration between most of the sampling locations. However, for S. guianensis, there was measurable migration in neighboring sampling locations. These results indicate that the small home ranges of these species may act to restrict gene flow between populations separated by relatively short distances, increasing the risk of extirpation of some localized populations in the future if existing threats are not minimized.